PEMANFAATAN KARET MENTAH PADA FLEXIBLE PAVEMENT LASTON AC-WC DAN LATASTON HRS-WC - Pataras, Mirka; Dewi, Ratna; Prasetya, Ahmad Dicky; Bazidno, Friko Denu (CANTILEVER, 2017)
With the many problems that begin to occur from the young asphalt cracked, the asphalt is not durable, the bumpy asphalt, and so it needs a new breakthrough to find a solution so that in the world of pavement in Indonesia can be better. The objective of this research is to add raw rubber or latex as an added ingredient of mixed laston (AC-WC) and lataston or HRS-WC as well as the effect of change of AC and HRS characteristics in addition to the percentage amount of raw rubber.This research was done by adding crude rubber on asphalt with percentage addition of 5%, 10% and 15%. The optimum asphalt content obtained from the mixture of normal test specimen as much as 15 specimens is 6.25% and from the bitumen content is then used to make asphalt raw rubber mixture as much as 3 specimens from each percentage of rubber addition. After that the research is continued by comparing the characteristics of the normal asphalt test results that have been in can with the addition of asphalt raw rubber mixture from each presentse is in search of the percentage addition of crude rubber included in the specification. From the result of this research, it is obtained that the optimum bitumen content at the normal mixture is 6,25% and the increase of optimal crude rubber percentage is at the crude rubber content 5% and 10% with the stability, melt and marshall quotient (MQ) value obtained appropriate and included in the specification of the test results marshall conducted.